2005
DOI: 10.1038/sj.jcbfm.9600158
|View full text |Cite
|
Sign up to set email alerts
|

Increased Perfusion in Motor Areas after Constraint-Induced Movement Therapy in Chronic Stroke: A Single-Photon Emission Computerized Tomography Study

Abstract: Hemiparesis is the most common deficit after cerebral stroke. Constraint-induced movement therapy (CIMT) is a new neurorehabilitation method that emphasizes task-relevant repetitive training for the stroke hand. Twelve chronic stroke patients were studied with single-photon emission computerized tomography at rest before and after the two-week CIMT period. Increased perfusion was found in motor control related areas. The specific areas with an increase in perfusion in the affected hemisphere were in the precen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…Forced use of the affected limb through constraint or motor skill learning after stroke has been shown to promote cortical remapping in periinfarct cortex in patients and promotes functional recovery in humans, nonhuman primates, and rats (32,33). Using the detail provided by quantitative projection mapping, modest axonal sprouting was found within primary motor and sensory areas with forced use of the affected limb in control animals and following stroke alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forced use of the affected limb through constraint or motor skill learning after stroke has been shown to promote cortical remapping in periinfarct cortex in patients and promotes functional recovery in humans, nonhuman primates, and rats (32,33). Using the detail provided by quantitative projection mapping, modest axonal sprouting was found within primary motor and sensory areas with forced use of the affected limb in control animals and following stroke alone.…”
Section: Discussionmentioning
confidence: 99%
“…In patients who have had a stroke, forced use of the affected limb promotes recovery of that limb and remapping of brain activity in periinfarct cortex (32)(33)(34). If the ephrin-A5 system plays a significant role in remapping motor system projections within periinfarct cortex, it is important to test the interaction of ephrin-A5 signaling with forced limb use.…”
Section: Ephrin-a5 Signaling Interacts With Patterned Behavioral Actimentioning
confidence: 99%
“…Our literature search identified 28 relevant training studies that quantified neural plasticity changes for further analysis to determine if inclusion in this meta-analysis was appropriate (Brouwer & Ambury, 1994;Carey et al, 2002;Cramer, 2004;Cramer et al, 1999;Cramer et al, 1997;Foltys et al, 2003;Jang et al, 2003;Jang et al, 2005;Könönen et al, 2005;Koski et al, 2004;Levy et al, 2001;Liepert, Bauder et al, 2000;Liepert, Graef et al, 2000;Liepert et al, 2001;Lindberg et al, 2004;Luft et al, 2004;Muellbacher et al, 2002;Nelles, 2004;Nelles et al, 2001;Newton et al, 2002;Park et al, 2004;Platz et al, 2005;Schaechter et al, 2002;Seitz et al, 2004;Sonde et al, 2001;Stinear & Byblow, 2004;Wittenberg et al, 2003). For meta-analysis inclusion, each article was originally examined for changes in neural representation measured in four areas of interest: (1) primary motor cortex (M1), (2) supplementary motor area, (3) dorsal premotor area, and (4) cingulate area.…”
Section: Subjects: Study Selection and Inclusion/exclusion Criteriamentioning
confidence: 99%
“…The 13 remaining studies (Carey et al, 2002;Jang et al, 2003;Jang et al, 2005;Könönen et al, 2005;Koski et al, 2004;Liepert, Bauder et al, 2000;Liepert et al, 2001;Luft et al, 2004;Muellbacher et al, 2002;Nelles et al, 2001;Platz et al, 2005;Schaechter et al, 2002;Stinear & Byblow, 2004) used upper extremity training as a rehabilitation treatment while testing stroke subjects in both the sub-acute and chronic stages of recovery. The necessary data from the 13 treatment studies were extracted by two authors and separately confirmed by the other three authors of this meta-analysis.…”
Section: Subjects: Study Selection and Inclusion/exclusion Criteriamentioning
confidence: 99%
“…There are many studies evaluating brain activation after stroke in patients submitted to a rehabilitation training. To our knowledge there is only one study with brain SPECT in this setting 6 . SPM is an automatic statistical analysis tool for neuroimaging.…”
mentioning
confidence: 99%